2023
DOI: 10.1037/cfp0000213
|View full text |Cite
|
Sign up to set email alerts
|

Digital interventions for couples: State of the field and future directions.

Abstract: Intimate relationship distress harms physical and mental health, and effective couple therapies are underutilized due to barriers to access. Digital couples' interventions (DCIs), including online and mobile programs, can improve access to effective relationship help. This paper outlines the state of the DCI field by describing seven currently available, empirically based DCIs and discussing key design and implementation issues along four key dimensions: Target populations, coaching, linked users, and intimate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 76 publications
0
7
0
Order By: Relevance
“…Research has shown that interventions addressing dyads can reliably improve DS and may be useful in this regard, but they should be tailored to the unique needs of MFCs, who are often different from their civilian counterparts. 45,46 For example, one study on caregivers using a psycho-education intervention for dyads (caregiver and care recipient) found positive effects on mental, emotional, and functional HOs, as well as on self-efficacy. 47 Likewise, on the basis of research supporting direct links between social support and DS, 17 behavioural interventions targeting mental HOs might consider incorporating strategies for enhancing social support and support networks.…”
Section: Discussionmentioning
confidence: 99%
“…Research has shown that interventions addressing dyads can reliably improve DS and may be useful in this regard, but they should be tailored to the unique needs of MFCs, who are often different from their civilian counterparts. 45,46 For example, one study on caregivers using a psycho-education intervention for dyads (caregiver and care recipient) found positive effects on mental, emotional, and functional HOs, as well as on self-efficacy. 47 Likewise, on the basis of research supporting direct links between social support and DS, 17 behavioural interventions targeting mental HOs might consider incorporating strategies for enhancing social support and support networks.…”
Section: Discussionmentioning
confidence: 99%
“…One approach to facilitating dissemination has been to translate skill-based workshops into brief self-directed online programs (see Knopp et al, 2021, for a review). Notable examples of this include the electronic version of the Prevention and Relationship Enhancement Program and OurRelationship, which have demonstrated benefits for relationships (e.g., Braithwaite & Fincham, 2009, 2011; Doss et al, 2016, 2019).…”
Section: Relationship Strengthening Interventionsmentioning
confidence: 99%
“…The seemingly inexorable direction of travel toward digital intimacies must therefore be embraced with some degree of caution. The rapid growth of the digital health market and ever‐increasing range of apps available need to be equally matched by robust multidimensional evaluations (Hay, 2016; Knopp et al, 2021) which are crucial for developing the evidence‐base for relationship interventions. Below we set out how evaluations of digital interventions might benefit from a practices approach and engage with the challenges to epistemological and ontological certainties posed by feminist new materialisms.…”
Section: Case Studymentioning
confidence: 99%